7 William Waller Hening, The Statutes at Large; a Collection of all the Laws of Virginia 35 (1820) - (:unkn) unknown (My University, 1756)
Prohibited Catholics from being armed and requiring oaths of allegiance and supremacy in front of justices of the peace.
Keywords: RELIGIOUS RESTRICTION